First checklist of the oribatid mites (Arachnida: Oribatida) of the Gran Chaco region (South America) with new records - Gomez Pamies, Diego Fernando (2023)
The South American Gran Chaco ecoregion extends through great areas of Argentina, Paraguay, Bolivia, and Brazil. The region includes vast forests that serve as an important reservoir of tropical and subtropical diversity. In spite of its extent and high biodiversity, it remains an unexplored area regarding Oribatida. We made bibliographic research about the oribatid mites previously registered. In the bibliography of Argentina and Paraguay, a total of 53 species are cited for this region. From our own works in the Argentinean provinces of Santiago del Estero and Chaco, we add some new records of Oribatida in the area. We provide a list of the species registered to date, including 48 firstly recorded in this work, as well as new localities for other 11 species previously known for the area. This paper almost doubles the number of registered species for this highly diverse but poorly known ecoregion, adding information towards the true diversity of Oribatida in the Chaco region.